Knowledge About Physiotherapy Profession Among High School Students - Arun Balasubramaniam; Illakiya B; Pavithra S; Maria Evagline Preetha; Amsa Palani; Akila M (JURNAL PROTEKSI KESEHATAN, 2021)
Physiotherapy is a branch of medicine and plays a vital role in preventing injuries, progression of health, and restoration of fitness. Professionally physiotherapy growth is much slower when compared with the other medical professionals, and the knowledge is low with the school students. This study is conducted to identify the knowledge of physiotherapy as a profession in school students. A descriptive study with 250 school students who are currently studying 10th grade & 12th grade were selected, and a self-designed questionnaire was circulated to them, and they have to answer on a 5-point Likert scale. One hundred seventy-five were eligible for the study, and data were analyzed using descriptive statistics. Results show that knew 50% about the sub-specialties, 70% & 60% have knowledge of treatment modalities and their uses in physiotherapy practice. This study concluded that high school students are having good awareness about physiotherapy as a profession. Further education to the schools is needed to enrich the knowledge about the physiotherapy profession to the school students.